Impacts de l’intervention comportementale intensive en contexte d’inclusion: Early intervention in daycare settings for children with pervasive developmental disorders : impacts on children and their parents - Normand, Claude L.; Moreau, André C.; Ruel, Julie; Bergeron, Sophie (Revue francophone de la déficience intellectuelle, 2009)
L’objectif de cette recherche vise à décrire les résultats d’un programme d’intervention comportementale intensive (ICI) en contexte d’inclusion sur le développement de l’enfant, sur sa participation sociale et celle de sa famille. Un échantillon de huit enfants entre 3 et 6 ans diagnostiqués TED a participé au programme sur des périodes variant entre 6 et 24 mois. Des mesures de développement et des indices de participation sociale ont été analysés. Les résultats suggèrent entre autres que la variation du développement est davantage en lien avec les caractéristiques de l’enfant avant l’entrée dans le programme que la durée de l’intervention. Également, la description de la participation sociale des enfants et de leurs parents permet de dégager les retombées d’un tel programme. Abstract This study describes outcomes on children with pervasive developmental disorders (PDD) of an intensive early intervention program implemented in a daycare setting. The outcomes measured are children’s developmental rate, their social participation as well as their parents’ social participation. Our sample consists of eight children between 3 and 6 years of age diagnosed with PDD. They had taken part in the early intervention program for at least 6 months and up to 24 months. Measures of development and social participation were taken before and after the intervention. Results suggest that variations in rates of development are linked to child characteristics before entry, rather than duration of the intervention program. Outcomes on social participation of children and their parents are also discussed.